Surgery-induced changes in rat IL-1β and acetylcholine metabolism: role of physostigmine - Plaschke, Konstanze; Müller, Ann-Katrin; Kopitz, Jürgen (Clinical and experimental pharmacology and physiology, 2014)
Pharmacological enhancement of cholinergic activity following administration of physostigmine is known to induce protective effects generally. However, it is unclear whether the effect of physostigmine on inflammation and acetylcholine (ACh) metabolism is related to different types of surgical intervention or anaesthesia alone. To investigate this, rats were subjected to partial liver resection (PLR) or sham surgery, with a control group receiving anaesthesia alone. Half of each treatment group received a single intra-operative dose of physostigmine (0.04 mg/kg); the others received placebo. Acetylcholinesterase (AChE) activity and plasma and brain concentrations of interleukin (IL)-1β and ACh were determined. Both PLR and sham operation induced a time-dependent increase in plasma concentrations of IL-1β compared with rats receiving anaesthesia alone (3.9- and 4.8-fold increases, respectively). In the brain, IL-1β concentrations had increased approximately twofold after surgery compared with the control group. Blood AChE was transiently decreased after surgery. Brain AChE activity increased 1.3-fold (P = 0.014) only after PLR; consequently, cerebral ACh concentrations were significantly reduced. Physostigmine administration significantly reduced IL-1β and AChE levels. Cerebral ACh concentrations were markedly increased from 544 ± 122 ng/mg protein following placebo administration to 654 ± 93 ng/mg protein after physostigmine administrations (P < 0.001). We conclude that a single dose of physostigmine intra-operatively has a sustained anti-inflammatory effect (up to 120 min after injection) that is especially pronounced under the conditions of PLR surgery. In addition to its protective peripheral action, physostigmine exerts a neuroprotective action by increasing levels of the neurotransmitter ACh.